2004
DOI: 10.1620/tjem.203.253
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperbaric Oxygen Treatment on Oxidant and Antioxidants Levels during Liver Regeneration in Rats

Abstract: The effects of hyperbaric oxygen (HBO) therapy on oxidant/antioxidant metabolism are controversial and its effects on hepatic regeneration are not known. In this study, we investigated a possible beneficial effect of HBO therapy on oxidant and antioxidants levels during liver regeneration. To conduct this study, seventy percent hepatectomy was performed on forty-eight SpraggueDawley rats and the rats were divided into two equal groups: HBO-treated group and untreated group (non-HBO group). We determined the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 69 publications
2
55
0
2
Order By: Relevance
“…On this basis, it is quite likely that the supply of oxygen at high pressure after I/R injury may act as a "protector" of the mitochondrial membrane. This "protection" is due to the fact that oxygen acts as an agent that permits the formation of ATP by means of oxidative phosphorylation, as also demonstrated in other studies 2,3,17 . This provides the energy needed for the occurrence of ion flow through the mitochondrial membrane, with consequent fluid inflow into the mitochondria.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On this basis, it is quite likely that the supply of oxygen at high pressure after I/R injury may act as a "protector" of the mitochondrial membrane. This "protection" is due to the fact that oxygen acts as an agent that permits the formation of ATP by means of oxidative phosphorylation, as also demonstrated in other studies 2,3,17 . This provides the energy needed for the occurrence of ion flow through the mitochondrial membrane, with consequent fluid inflow into the mitochondria.…”
Section: Discussionsupporting
confidence: 57%
“…This fact was not observed in other studies, in which the SHAM and IR groups already presented some difference [10][11][12]16 . In those studies there was an increase in the rate of oxygen consumption by the mitochondria compared to the SHAM group in order to maintain the electrochemical proton gradient on the mitochondrial membrane so that the membrane would be able to phosphorylate ADP 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Gunel et al (1999) found that MDA levels increase in the early phase (first 24, 48 and 72 hours) of corrosive esophagitis. Ozden et al (2004) used MDA as an indicator of free radical generation in their study. We found that MDA level significantly increased in early phase of corrosive esophagitis (first 24 hour) and significantly decreased by trapidil treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that this treatment operates with two physical factors of the hyperbaric chamber: effects of mechanical stress and increased tissue oxygenation 11 . The use of HBO in the I/R damage is controverse, because it was believed that its use would increase tissue damage by raising the level of oxygen and consequently the level of reactive species and free radicals in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…The use of HBO in the I/R damage is controverse, because it was believed that its use would increase tissue damage by raising the level of oxygen and consequently the level of reactive species and free radicals in the blood. However, there are studies that show positive changes caused by its use, suggesting a protective effect in different tissues [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%